The postnatal development of the human cardiac ventricles - Keen, Edward Norman (Division of Cardiology, 2020)
The name of William Harvey is imortal, and it is fitting that a quotation form his epoch-making 'De Motu Cordis et Sanguinis' should preface this thesis. the discoverer of the circulation did not fall to point out the difference between foetal and postnatal conditions of the heart and great vessels. Harvey, however, was not particularly concerned with the problems of the foetal circulation, and devoted only a passing glance to the subject, using foetal conditions to illustrate his general argument about the circulation of the blood. The subsequent progress of though on the subject of foetal circulation has been admirably set out in the first chapter of Barclay, Frankin, and Prichard's book 'The Foetal Circulation', published in 1944, but there is no doubt that the major advance since Harvey's time is represented by the cine-radiographic observations made by the authors of this book on the foetal lamb. They provided, for this species, a convincing and complete picture of the pattern of the foetal circulation, together with the change brought on by allowing the foetus to breathe and by severing the umbilical cord, thus simulating the event of birth.